2018
DOI: 10.1007/s00432-018-2613-9
|View full text |Cite
|
Sign up to set email alerts
|

Young adults diagnosed with Hodgkin lymphoma are at risk of relapsing late: a comprehensive analysis of late relapse in Hodgkin lymphoma

Abstract: Late relapse of HL presents with clinical characteristics very similar to primary disease and appears to have a good prognosis. First diagnosis in childhood or young adulthood and first line treatment before the ABVD era increases the risk of relapsing late.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 26 publications
1
16
2
Order By: Relevance
“…In accordance with a previous report, 13 we found inferior OS in cHL patients with LR compared with patients in cCR. In the present study, cHL experiencing LR had an almost threefold increased risk of death compared with patients in cCR 4,7,9–11,15 . A number of previous studies on LR in HL do not report significant differences in OS between LR and cCR patients.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…In accordance with a previous report, 13 we found inferior OS in cHL patients with LR compared with patients in cCR. In the present study, cHL experiencing LR had an almost threefold increased risk of death compared with patients in cCR 4,7,9–11,15 . A number of previous studies on LR in HL do not report significant differences in OS between LR and cCR patients.…”
Section: Discussioncontrasting
confidence: 52%
“…With rare exceptions, 15 most studies found increasing age to be an independent risk factor for LR 10,12,13,30 . This observation could reflect the fact that older patients receive less intensive front‐line treatment and/or have a senescent, altered host immune system including different tumour micro‐environmental features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations